Hollow Ring-Core Photonic Crystal Fiber With >500 OAM Modes Over 360-nm Communications Bandwidth - Yingning Wang; Yao Lu; Changjing Bao; Wenpu Geng; Yuxi Fang; Baiwei Mao; Zhi Wang; Yan-Ge Liu; Hao Huang; Yongxiong Ren; Zhongqi Pan; Yang Yue (IEEE Access, 2021)
We propose and design a hollow As2S3 ring-core photonic crystal fiber (PCF) with 514 radially fundamental orbital angular momentum (OAM) modes over 360 nm communications bandwidth across all the O, E, S, C, and L bands. The designed PCF with 40 $μ \text{m}$ -radius air core and 150 nm-width As2S3 ring can support eigenmodes up to HE130,1 and EH128,1. The numerical analysis shows that the designed ring PCF has large effective refractive index contrast, and can transmit up to 874 OAM modes near 1.55 $μ \text{m}$ . Simulation results show that in the C and L bands, the PCF with a hollow-core radius of 40 $μ \text{m}$ and a ring width of 0.15 $μ \text{m}$ can retain an $2.5× 10 ^{-3}$ effective refractive index difference between the two highest order OAM modes, which achieves effective mode separation, thereby achieving stable OAM mode transmission. The $n_{eff}$ difference between the even and odd fiber eigenmodes and the intra-mode walk-off are also carefully studied under different bending radii. The results show that higher-order OAM modes has better tolerance to the fiber bending, compared with the lower-order modes. The fiber has the potential to support ultra-high capacity OAM mode division multiplexing in the optical fiber communication systems.